Utilization of sheep dung and rice straw with indigenous microbial agent to optimize vermicompost production and quality (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Hidayati YA, Nurachma S, Badruzzaman DZ, Marlina ET, Harlia E. 2021. Utilization of sheep dung and rice straw with indigenous microbial agent to optimize vermicompost production and quality. Biodiversitas 22: 5445-5451. Sheep dung is a useful by product that can be potentially processed into more useful products with minimal pollution. Vermicomposting is a waste processing method that produces Solid Organic Fertilizer and worm biomass as the raw materials for drugs and cosmetics. This research aimed to utilize the role of indigenous fungi and bacteria to determine the influence of C/N ratio from sheep dung and rice straw mixture on vermicompost quality (N, P, K, Ca, Mg). This experimental research was conducted in a Completely Randomized Design with three treatments (T1: C/N ratio of 25; T2: C/N ratio 30; T3: C/N ratio 35) and six replicates for each treatment. Data so obtained were analyzed with ANOVA and Duncan's Multiple Range Test. The results showed that C/N ratio had a noticeable influence on vermicompost quality. C/N ratio 30 produced the highest vermicompost quality (N: 1.11 ± 023381%; P: 0.56 ± 0.010328 %; K: 0.51 ± 0.021369 %; Ca: 0.33 ± 0.0248 %; Mg: 0.14 ± 0.0228%).
Keywords: C/N ratio; Indigenous Microbes; Rice Straw; Sheep Dung; Vermicomposting